Professionalism in Medical Education - Muna A. M. Elnemr (Yemeni Journal for Medical Sciences, 2010)
It is unambiguous that the moral codes and ethics of the medical profession are threatened at the present point in time by the progressive invasion of commercialism into the field of medicine. Medical education worldwide must take greater responsibility and liability for reforming the making of future doctors to uphold their commitment to the ethics of medicine. This target can be achieved by improving professionalism. The current trend in teaching and evaluating professionalism for medical students and residents has put heavy demands on medicine's educational institutions. Professionalism must be taught explicitly and evaluated effectively. However, many faculty members do not possess the necessary knowledge and skills to teach this content area and faculty development is therefore required. A specially developed program that provides the teaching and evaluation of professionalism can help in significant improvement in medical education. This review will discuss different challenges facing teaching professionalism and the methods of its assessment.